2020
DOI: 10.3390/w12030902
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Scour Rates Prediction-Based Model Utilizing a Multilayer Perceptron-Colliding Body Algorithm

Abstract: In this research, the advanced multilayer perceptron (MLP) models are utilized to predict the free rate of expansion that usually occurs around the pipeline (PL) because of waves. The MLP model was structured by integrating it with three optimization algorithms: particle swarm optimization (PSO), whale algorithm (WA), and colliding bodies’ optimization (CBO). The sediment size, wave characteristics, and PL geometry were used as the inputs for the applied models. Moreover, the scour rate, vertical scour rate al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The AI models considered benefit from two intrinsic advantages: The first merit is to drive regression-based equations along with highlighting the physical meaning of the experimental observations; the second remarkable merit is associated with the upscaling of datasets. In this way, the dimensionless structure of equations given by the proposed AI models would be applicable at various scales from laboratory to field studies (e.g., Parsaie et al [18], Najafzadeh and Saberi-Movahed [26], Ehteram et al [27], and Sharafati et al [30]).…”
Section: Intelligent Computing Methods: Brief Descriptions and Implementationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The AI models considered benefit from two intrinsic advantages: The first merit is to drive regression-based equations along with highlighting the physical meaning of the experimental observations; the second remarkable merit is associated with the upscaling of datasets. In this way, the dimensionless structure of equations given by the proposed AI models would be applicable at various scales from laboratory to field studies (e.g., Parsaie et al [18], Najafzadeh and Saberi-Movahed [26], Ehteram et al [27], and Sharafati et al [30]).…”
Section: Intelligent Computing Methods: Brief Descriptions and Implementationsmentioning
confidence: 99%
“…From their study, GMDH-GEP indicated relatively better performance in the prediction of three-dimensional free spans than GEP, GMDH, and empirical equations. Moreover, Ehteram et al [27] applied new improvements of ANN, by Colliding Bodies' Optimization (CBO), to model the three-dimensional nature of scour below seabed pipelines. Ultimately, they concluded that the improvement of the application of CBO into ANN resulted in more accurate predictions than PSO and the Whale Algorithm (WA).…”
Section: Wave-induced-pipeline Scourmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decades, the hydrologists have popularly used the soft computing methods for streamflow modeling. Since Artificial Neural Network (ANN) has ability to model linear and non-linear systems even without making any assumption, the models of ANN were widely used in various water science subjects [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%